Teachers' Perceived Work Autonomy in Iranian Public Schools - Habib Soleimani; Naser Shirbagi (Engiscience Publisher, 2024)
The purpose of this study is to investigate the concept of teachers' work autonomy of a sample of Iranian teachers and examine the level of this perceived autonomy based on some demographic variables. The design was a quantitative-descriptive survey, whose population was all teachers in Sanandaj, a city in Iran. The sample was taken based on cluster sampling according to Krejcie Morgan table. The data collection tool, the Teachers' Appropriate Work Autonomy Questionnaire, was adapted from Friedman (1999) which assesses the extent to which teachers' routine activities should be performed autonomously by the teachers themselves. In order to test the content validity of the teachers' work autonomy questionnaire, a confirmatory factor analysis was run. To test the hypotheses, one-sample t-test, independent sample t-test, and one-way analysis of variance (ANOVA) tests were run. Findings showed that teachers rated their levels of work autonomy lower than the mean level of the relevant scales. Teachers had rated their autonomy below the mean in establishing school identity and praxis, parental involvement, staff development, and extracurricular subjects. Furthermore, their self-assessment for the degree of autonomy in teaching and achievement evaluation was close to the mean, while for curriculum change and development, it was above the mean. Regarding demographic variables, there were significant differences between the degree of teachers' work autonomy in academic degrees, teaching level, and academic degree. However, there was no significant difference between the mean scores of teachers' self-assessments regarding their level of work autonomy in terms of gender and teaching experience.